On the question of the syllabic system of versification: the poetic practice of Theophan Prokopovich - Natalia V. Patroeva (Слово.ру: балтийский акцент)
The study is devoted to the analysis of the accentual architectonics of the isosyllabic works of Theophan Prokopovich. The primary objective of this analysis was to examine the hypothesis regarding the gradual emergence of the syllabo-tonic system within the framework of syllabic verse. This hypothesis challenges the views of numerous scholars of versification, who argue for a revolutionary shift in Russian poetic tradition, attributed to the publication of Vasily Trediakovsky's 1735 treatise. Additionally, the study aims to compare the theoretical recommendations outlined in Prokopovich's poetics and rhetoric with his own experiments in versification. The most common form in Theophan's poetry, as well as in the works of the Virsheviks—his predecessors and contemporaries—is the thirteen-syllable verse. This form is genre- and theme-diverse, appearing in odes, epigrams, inscriptions, occasional poems, and humorous poem cycles. However, it is less metrically ordered compared to other types of syllabic verse and exhibits the greatest diversity in accent placement. It actively demonstrates the "inverted rhythm" described by A. P. Kvyatkovsky and shows the least tendency toward a "fixed" rhythm. Eleven-syllable verses, found in epitaphs, psalm adaptations, messages, epigrams, and occasional poems, are somewhat less common in Theophan's lyrics. Octosyllabic and heptosyllabic verses are rare, while a single example of a decasyllabic verse is present in his body of work. The "incorrect" lines in isosyllabic verses turn out to be marginal, which, along with the increase in the number of repeating accent patterns in Theophan's poems, speaks of the high development of the verse technique in the post-Petrine era. The norms of the future syllabo-tonic system gradually, slowly, but steadily developed in the depths of verse poetry. Thus, Theophan’s 11-, 10- and 8-syllable verses, as well as non-isosyllabic cants and arrangements of psalms, demonstrate a high (reaching the level of ideal trochaic, iambic, anapestic and dactylic lines) degree of rhythmic orderliness, supported by anaphoric repetitions, internal rhymes, rare inter-verse hyphenations, which together bring the rhythm and intonation of Theophan's elegies, cants and songs closer to the melodious syllabo-tonic verse, while the thirteen-syllable verses and some humorous heterosyllabic verses are saturated with conversational and declamatory intonations. The results of the analysis confirm the reformist role of Theophan Prokopovich in the field of ordering syllabic versification, which evolved in the direction of metrotonicity.